INVOLVEMENT IN PRESCHOOL EDUCATION AND PRIMARY EDUCATION: BASED ON INFORMATION COMMUNICATION TECHNOLOGIES - Rejapova Namunaxon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article sees the problems of digitalization of all aspects of our life, including the role of digital technologies in the integration of preschool and primary education, digitalization. The article discusses the actual problems of the theory and methodology of the application of information and communication technologies and digital technologies as a means of the modern educational process, which increases the cognitive activity, worldview and motivation of preschool and Primary Education Children, which are considered an important need of the current era of globalization. The application of digital technologies in the process of education and upbringing was mentioned about the guarantees of the achievements of preschool children and, subsequently, guarantees of successful schooling at school.